Oesopbageal end-to-end anastomosis by inverting and everting techniques in dogs - Kumar, Naveen; Chaudhary, R J (The Indian Journal of Animal Sciences, 2012)
End-to-end experimental anastomosis of cervical oesophagus was performed in dogs by inverting and everting suture techniques using catgut No. 3/0 and silk No. 3/0 suture materials. Macroscopic examination revealed leakage and fistula formation in everting technique whereas fair healing with normal lumen size was observed in inverting technique.